Optymalizacja Parametryczna Układu Drgającego o Dwóch Stopniach Swobody - Olszowski, B. (Engineering Transactions, 1970)
Discussed here is the problem of the optimum shaping of a vibrating cantilever system in steady state under the influence of harmonic force acting on one of the concentrated masses. The shaping is carried out with a fixed structure of the system through an optimum selection of two independent parameters which determine the ratios of the masses and rigidities by the way of minimization of the amplitude of elastic energy of the system. Practical rules of selection of parameters arc given for two cases of forcing acting either on one concentrated mass, or the other, together with a nomogramme determining the mutual dependence between the eigen frequencies and the parameters of optimization.The results of the considerations are illustrated by a numerical examples.